Keep off the grass? No way!: The use of indirect translation for public signs will never result in 'an attractive linguistic landscape' unless it promotes and spreads the cultural values of the literal translation. Issue 1 (18th December 2015) - Hu Xiaoqiong, Betsy
Abstract : China's rapid economic development has helped to raise the international status of Mandarin. One prediction is that 'in ten years, Mandarin will be as important worldwide as English' (Trudgill, 2014: 387). Another even greater change resulting from China's economic growth is the increasing popularity that English enjoys in China (Hu, 2004, 2005; Hu, 2009; Zhang, 2012; Werner, 2014). English is now used in a wide range of fields and contexts throughout the country. This is not surprising given the dominance of the English language on a global scale. English, now increasingly employed together with Chinese to combine global with local appeal, functions 'as an index of modernity, progress, internationalism and globalization, a symbol of success, sophistication and projection into the future' (Vettorel, 2013: 262). One indicator illustrating this phenomenon is the widespread use of public signs in both Chinese and English. Some authors argue that this use of bilingual signs has resulted in the creation of 'an attractive linguistic landscape' in China (Yang & Liu, 2008:79). Accordingly, research on bilingual public signs has, in recent years, become 'a hot area in the translation field' (Zou et al, 2011:27), attracting the attention of a growing number of scholars (e.g. Dai & Lü, 2005; Song, 2013; Chen, 2014).